A p-star model approach on inflation in Singapore and the Philippines - Lee, Hui Zhi (Universiti Malaysia Sarawak, (UNIMAS), 2010)
‘Inflation is always and everywhere a monetary phenomenon’, a famous phrase by Milton Friedman, has always been a hot topic. Thus, this subject regarding ‘monetarist’ view is still been questioned until now. A stable relationship between price level and monetary aggregate is crucial as this monetary aggregate would be a good predictor of inflation. Therefore, determining which monetary aggregate is better in monitoring to produce an effective monetary policy is crucial as well. Since 1980s, the increase of financial liberalization and innovation blurred the relationship between money and price. Therefore, the weaknesses of traditional Simple Sum monetary aggregates led to the introduction of Divisia monetary aggregates. By using P-Star model framework, the performances of Divisia monetary aggregates are investigated to predict the inflationary movement against their Simple sum counterparts. In this paper, Singapore and the Philippines are examined to ascertain an appropriate monetary aggregate in monitoring their monetary policy respectively. As a result, it was discovered that Simple sum M2 exhibited more information contents in predicting inflationary movement in Singapore whereas Simple sum M1 is superior in the Philippines. Lastly, P-Star model sought be a valid empirical model to predict inflation for Singapore and the Philippines.